2004
DOI: 10.1002/jnr.20071
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of doublecortin expressing cells near the lateral ventricles in the adult mouse brain

Abstract: Doublecortin (Dcx) is a microtubule-associated protein expressed by migrating neuroblasts in the embryo and in the adult subventricular zone (SVZ). The adult SVZ contains neuroblasts that migrate in the rostral migratory stream (RMS) to the olfactory bulbs. We have examined the distribution and phenotype of Dcx-positive cells in the adult mouse SVZ and surrounding regions. Chains of Dcx-positive cells in the SVZ were distributed in a tight dorsal population contiguous with the RMS, with a separate ventral popu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
99
0
1

Year Published

2004
2004
2013
2013

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 116 publications
(110 citation statements)
references
References 53 publications
10
99
0
1
Order By: Relevance
“…We found that the basal levels of cells incorporating BrdU in the hippocampus and SVZ of sham-operated control animals were consistent with those of previous reports (Kempermann and Gage, 2000;Mandairon et al, 2003;Brown et al, 2003;Yang et al, 2004). In the SVZ, BrdUpositive cells were concentrated in a tight band in the dorsal area (Figure 1a), and in a looser network of single cells in the ventral area.…”
Section: Resultssupporting
confidence: 92%
“…We found that the basal levels of cells incorporating BrdU in the hippocampus and SVZ of sham-operated control animals were consistent with those of previous reports (Kempermann and Gage, 2000;Mandairon et al, 2003;Brown et al, 2003;Yang et al, 2004). In the SVZ, BrdUpositive cells were concentrated in a tight band in the dorsal area (Figure 1a), and in a looser network of single cells in the ventral area.…”
Section: Resultssupporting
confidence: 92%
“…It was also recently reported that TuJ1-positive cells in the SVZ and RMS stain positive for doublecortin, an additional neuronal precursor marker (Yang et al, 2004). The exclusive presence of neuronal precursors in the anterior SVZ and RMS is consistent with the time course of gliogenesis that ceases at ϳ14 -15 d of age in rats (Levison and Goldman, 1993).…”
Section: Characteristics Of Neuronal Precursor Migration In the Antersupporting
confidence: 74%
“…5f-h). We also observed that in tamoxifentreated Nestin CreER/ϩ ; Smo c/c mice, the expression of Mash1 (C cell marker) (Parras et al, 2004), Dcx (A cell marker) (Francis et al, 1999;Gleeson et al, 1999;Englund et al, 2002;Brown et al, 2003;Yang et al, 2004) and GFAP (B cell marker, but also marker of mature astrocytes; Doetsch et al, 1997Doetsch et al, ,1999a is reduced (Fig. 6) Fig.…”
Section: Generation Of a Nestinmentioning
confidence: 54%